Life events and rites of passage : the customs and symbols of major life-cycle milestones, including cultural, secular, and religious traditions observed in the United States - Hill, Jeff, 1962-; Becker, Peggy Daniels (Detroit, MI : Omnigraphics, 2008)
"Provides information about the history, symbols, customs, and traditions of important life-cycle events within the broad range of cultural and religious groups in the United States. Entries are arranged in sections on birth and childhood, coming of age, adulthood, and death and mourning"--Provided by publisher.
pt. 1. Birth and childhood. Conception and pregnancy -- Greeting the baby -- Naming the baby -- Entering the faith -- Firsts -- Commemorating birth -- pt. 2. Coming of age. Religious milestones -- New privileges and responsibilities -- School events -- Revived and reinvented initiation rites -- pt. 3. Adulthood. Courtship -- Getting engaged -- Wedding preparations -- Wedding ceremonies -- Wedding receptions -- Post-wedding events -- Adult milestones -- Later adulthood -- pt. 4. Death and mourning. Preparing the body -- Funerals and other immediate mourning rituals -- Burials -- Memorials and later commemorations.
Includes bibliographical references and index.
Keywords: Rites and ceremonies -- United States; United States -- Social life and customs